THE ROLE OF VILLAGE GOVERNMENT AND TRADITIONAL INSTITUTIONS IN IMPLEMENTING SOLO HULIR SE'ANG HALA TRADITIONAL LAW IN KOTING D VILLAGE, SIKKA DISTRICT - Paulina Lawi; Danar Aswim; Rodja Abdul Natsir (Institut Pendidikan Indonesia, 2021)
This research aims to determine the extent of the role of the Village Government and Traditional Institutions in implementing Customary Law and the Effectiveness of Implementing Customary Sanctions according to Village Regulation Number 07 of 2018 concerning the Implementation of Customary Sanctions Solo Hulir Sea'ng Hala. This research method was carried out using a qualitative descriptive approach. The data sources used are primary data sources and secondary data sources. The informants involved in the research were the Village Head, Traditional Leader and BPD. The data collection techniques used were observation, interviews and documentation studies. Data analysis techniques include data collection, data reduction, drawing conclusions and verification. The research results show that the role of the Village Government is as a Mediator, Facilitator, Motivator, Justice of the Peace and Traditional Institutions play the role of a Mediator, Regulator, Justice of the Peace. The effectiveness of the implementation of customary sanctions by the Koting D Village Government can be said to be effective, because the implementation of customary sanctions is truly carried out and precisely according to its target and before being implemented, these rules are first disseminated to the community so that the community understands the regulations that have been made.